REINTERPRETASI HAK-HAK EKONOMI PEREMPUAN DALAM ISLAM - Nur Hidayah (Universitas Islam Negeri Jakarta, 2014)
Reinterpretation of Women’s Economic Rights in Islam. Islam prescribes equal rights for men and women, including economic rights. However, patriarchal interpretations of Alquran and Suna texts have contributed to a gender gap in which Muslimah women face difficulties in accessing their economic rights. Patriarchal structures that prescribe role divisions in society marginalise women from economic participation and property ownership. Contemporary Muslimah women also face similar problems of gender gap in economy. Therefore progressive Muslims offer reinterpretation of texts regarding women’s rights, including economic rights, using women’s perspectives. Such reinterpretation is also complemented with strategies of women’s economic empowerment to assist them to access their economic rights, particularly their rights of economic participation and access to paid employment.DOI: 10.15408/ajis.v14i1.1245